2020
DOI: 10.34172/jlms.2020.31
|View full text |Cite
|
Sign up to set email alerts
|

Photoelimination Potential of Chitosan NanoparticlesIndocyanine Green Complex Against the Biological Activities of Acinetobacter baumannii Strains: A Preliminary In Vitro Study in Burn Wound Infections

Abstract: Introduction: Acinetobacter baumannii strains are important agents causing serious nosocomial infections including soft-tissue and skin infections in patients with burn wounds which have become resistant to several classes of antibiotics. Antimicrobial photodynamic therapy (aPDT) as an alternative antimicrobial procedure is suggested for the treatment of these kinds of infections. The aim of the current study is to evaluate the antibacterial and anti-biofilm efficiency of aPDT by the utilization of an improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…The difference in the antimicrobial activities against MDR A. baumannii were dependent on the different concentrations of the tested CNPs. Our results are in line with other two previous studies conducted by Cobrado et al 70 and Pourhajibagher et al 71 Interestingly, Pourhajibagher et al proved that CNPs produced significant reduction of 93.2% on the viable count of planktonic and of 55.3% on the biofilm formation of A. baumannii strains as compared to the control group. 71 Furthermore, the activities of CNPs (5 mg/mL) when combined with CT, TGC or MEM, CT+MEM and TGC+MEM were evaluated via measuring the MDF as previously reported.…”
Section: Discussionsupporting
confidence: 93%
“…The difference in the antimicrobial activities against MDR A. baumannii were dependent on the different concentrations of the tested CNPs. Our results are in line with other two previous studies conducted by Cobrado et al 70 and Pourhajibagher et al 71 Interestingly, Pourhajibagher et al proved that CNPs produced significant reduction of 93.2% on the viable count of planktonic and of 55.3% on the biofilm formation of A. baumannii strains as compared to the control group. 71 Furthermore, the activities of CNPs (5 mg/mL) when combined with CT, TGC or MEM, CT+MEM and TGC+MEM were evaluated via measuring the MDF as previously reported.…”
Section: Discussionsupporting
confidence: 93%
“…55.3% compared to the ICG irradiated group with ca. 46.2%, which was also evident in the disrupted biofilm architecture viewed through SEM [ 219 ]. A closer observation of the effects exerted by chloroaluminium phthalocyanine (ClAlPc) encapsulated in CHNPs towards the biofilms of S. mutans ATCC 25175 at an irradiation dose of 100 J cm −2 through SEM revealed that the cells were irregularly shaped and arranged in shorter chains [ 220 ].…”
Section: Nanotechnology and Microtechnology In Antimicrobial Resismentioning
confidence: 94%
“…Chitosan nanoparticles have some advantages, such as being nontoxic, low immunogenic and biodegradable. In this regard, Pourhajibagher et al observed that, using a diode laser as a light source in a wavelength of 810 nm exposure, the PS indocyanine green encapsulated in chitosan NPs caused significant disruption to preformed biofilms by A. baumannii isolates from burn wounds, as also confirmed by SEM analysis [ 158 ]. In another study, Fekrirad et al found that chitosan at 1/2× MIC enhanced the antibiofilm efficacy of erythrosine-mediated-PDI against A. baumannii preformed biofilm causing a marked decrease in the number of viable biofilm cells (>3 log10 colony forming units, CFU/mL) [ 188 ].…”
Section: Prevention and Treatment Strategies Against A Baummentioning
confidence: 97%